The Street Lamp Paradox: Analysing Students’ Evaluation of Teaching through Qualitative and Quantitative Approaches - Patrizia Maria Margherita Ghislandi; Juliana Elisa Raffaghelli; Albert Sangrà; Giuseppe Ritella (Journal of Educational, Cultural and Psychological Studies, 2020)
This paper presents a study about Students Evaluation of Teaching (SET). Student surveys delivered at the end of the academic course is an approach currently applied in all Italian university courses. However, the quality of teaching is a multi-layered phenomenon whose evaluation might require additional methods. In this study, concerning a course offered during the academic year 2016/2017, we propose the qualitative analysis of students’ final essays, which includes the students’ opinion about teaching quality. The qualitative evaluation of teaching is then compared with the results of the standard SET survey. 48 students filled in the survey, while 47 delivered their final essay (a corpus of about 650 text pages). Our study shows that while the standard survey provides an overall picture useful at institutional level for Quality Assurance (QA), the qualitative approach captures an accurate account of students’ reactions, sensitive to the pedagogical approach adopted. This provides additional information on the students’ perspectives regarding the specific features of the course. Our case study suggests that the integration of traditional SET survey with qualitative teaching evaluation approaches, at least for innovative courses based on socio-constructivist learning, might provide information, overlooked in the Italian SET survey, that is useful for Quality Enhancement (QE) of teaching.